2021
DOI: 10.13057/biodiv/d220603
|View full text |Cite
|
Sign up to set email alerts
|

Soil macrofauna diversity in andisol after eight years of Mount Sinabung eruption in Sumatra, Indonesia

Abstract: Abstract. Sembiring M, Munawaroh H, Mukhlis, Hidayat B, Sabrina T. 2021. Soil macrofauna diversity in andisol after eight years of Mount Sinabung eruption in Sumatra, Indonesia. Biodiversitas 22: 3024-3030. The eruption of Mount Sinabung resulted in volcanic ash covering the soil of various thicknesses. That will affect the population and diversity of macrofauna in it. This research aimed to determine the Andisol soil macrofauna in Karo District with various thicknesses of volcanic ash covering from Mount Sina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…The distribution then decreases from the surface to the depth. Our work is similar to that of Sembiring et al (2021) who showed that the thickness of an Andisol strongly influences the vertical distribution and diversity of the macrofauna.…”
Section: Discussionsupporting
confidence: 91%
“…The distribution then decreases from the surface to the depth. Our work is similar to that of Sembiring et al (2021) who showed that the thickness of an Andisol strongly influences the vertical distribution and diversity of the macrofauna.…”
Section: Discussionsupporting
confidence: 91%
“…The samples were subjected to chemical analysis in a lab. Percentage of soil moisture was determined by collecting samples from 15 cm soil depth and measuring the dry and wet weight of the sample [2], Percentage of matter and organic carbon was measured using Walky-black method, Electrical conductivity was measured using soil saturated extract [8], Nitrogen was measured using Kjeldahl's measurement technique, Phosphorus was calculated using the technique proposed by Olsen Ribeiro et al [26], potentiometric acidity was measured using a pH meter [12], soil texture was calculated using Bukas hydrometry method, and bulk density was measured using the agglomeration method). In order separate macrofauna, a soil sample collected by the sampling frame was dumped on the surface of a nylon, then the macrofauna was carefully separated, and placed in 70% alcohol for identification.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, soil is recognized as a globally important reservoir of biodiversity because macrofauna is an important component of soil biodiversity [7][8][9][10]. Macrofauna can be used as a biological indicator of the impacts on land use, for its relationship with the physical and chemical properties of the soil, and for its rapid variation over a short period of time that is a product of changes in cover and transformation in vegetation [3,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those values indicate hydrogen ion concentration in the soil, in which the higher the H + content, the more acidic the soil. The pH affect the living of microorganisms in the soil [13].…”
Section: Physical and Chemical Characteristics Of Toba Peatlandmentioning
confidence: 99%